AÇÃO DE CINZAS DE INCINERADOR DE LIXO SÓLIDO URBANO COMO CORRETIVO DA ACIDEZ DE SOLOS - Chitolina, José Carlos; Feliconio, Ana Elisa Galante; Carmo, Janaína Braga do; Oliveira, Fernando Carvalho; Lavorenti, Arquimedes (REVISTA DE AGRICULTURA, 2020)
AÇÃO DE CINZAS DE INCINERADOR DE LIXO SÓLIDO URBANO COMO CORRETIVO DA ACIDEZ DE SOLOS